Production of (+)-globulol needle crystals on the surface mycelium of Quambalaria cyanescens - Stodůlková, E; Sulc, M; Císarová, I; Novák, P; Kolarík, M; Flieger, M (Folia microbiologica, 2008)
The structure of unique colorless needle crystals growing from the surface mycelium of the basidiomycete Quambalaria cyanescens and identified as (+)-globulol was followed by mass spectrometry, X-ray diffraction, and polarimetry. The mechanism of (+)-globulol fragmentation is proposed based on collision induced dissociation mass spectrometry. X-Ray analysis revealed that crystal packing is governed by hydrogen bond O-H.....O connecting the molecules into an infinite helix along a 3-fold screw axis propagating along the longest dimension of the needle crystal (c-axis of the unit cell). The X-ray diffraction data correspond well with the proposed structure determined by mass spectrometry.
Keywords: Molecular Structure; Basidiomycota; hmotnostní spektrometrie; mycelium; X-Ray Diffraction; seskviterpeny; Coleoptera; vodíková vazba; Mass Spectrometry; Animals; difrakce rentgenového záření; zvířata; Hydrogen Bonding; molekulární struktura; Mycelium; Crystallization; brouci; krystalizace; Sesquiterpenes